The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/molecules23092335
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protein Kinase Inhibitors Related to Tau Pathology Modulate Tau Protein-Self Interaction Using a Luciferase Complementation Assay

Abstract: The current number of drugs available for the treatment of Alzheimer’s disease (AD) is strongly limited and their benefit for therapy is given only in the early state of the disease. An effective therapy should affect those processes which mainly contribute to the neuronal decay. There have been many approaches for a reduction of toxic Aβ peptides which mostly failed to halt cognitive deterioration in patients. The formation of neurofibrillary tangles (NFT) and its precursor tau oligomers have been suggested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…CDK1 can phosphorylate Aβ at Ser26 increasing its neurotoxicity and reducing its ability to form insoluble fibrils [ 391 , 392 ]. CDK1 and CDK2 also contribute to Tau hyperphosphorylation [ 201 , 393 , 394 , 395 , 396 ]. In cell culture experiments, toxicity by Aβ was shown to involve induction of CDK2 activity and its phosphorylation of Tau [ 397 ] ( Figure 1 C)…”
Section: The Enzymesmentioning
confidence: 99%
“…CDK1 can phosphorylate Aβ at Ser26 increasing its neurotoxicity and reducing its ability to form insoluble fibrils [ 391 , 392 ]. CDK1 and CDK2 also contribute to Tau hyperphosphorylation [ 201 , 393 , 394 , 395 , 396 ]. In cell culture experiments, toxicity by Aβ was shown to involve induction of CDK2 activity and its phosphorylation of Tau [ 397 ] ( Figure 1 C)…”
Section: The Enzymesmentioning
confidence: 99%
“…FA analogs 17 and 18 were synthesized via the Williamson ether synthesis of 15 and 16 with alkyl/aromatic halide followed by sodium hydroxide mediated hydrolysis (Scheme 3). 22 Compounds 20–22 were obtained from 19 by an alkylation or amidation (Scheme 4) with alkyl halide, acyl chloride, or sulfonyl chloride 23–25 …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the efficacy of various antiepileptic drugs (AEDs) has been tested in epilepsy experimental models and in AD patients, showing a promising function in cognitive impairment prevention (Sánchez et al, 2018). Since tau hyperphosphorylation is the main mechanism responsible for NFT formation, it has been suggested that inhibiting different tau kinases such as CDK5 and GSK3β, involved in tau hyperphosphorylation, could reduce their aggregation (Xie et al, 2017;Holzer et al, 2018), observed in AD (Morris et al, 2011) and epilepsy (Sen et al, 2007;Thom et al, 2011;Tai et al, 2016).…”
Section: Therapeuticsmentioning
confidence: 99%